2001
DOI: 10.5488/cmp.4.3.473
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Liquid Alkali Metals

Abstract: The internal energy, entropy and Helmholtz free energy of liquid alkali metals, viz. Na, K, Rb and Cs are investigated using pseudopotential perturbation scheme based on Gibbs-Bogoliubov variational technique. A local pseudopotential is applied to describe the electron-ion interaction in the liquid alkali metals. To introduce the exchange and correlation effects, the local field correction function proposed by Taylor is employed. The computed values for internal energy, entropy and Helmholtz free energy for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…It also shows that the change in trend, the deviation of our results from experimental values of the internal energy EINT in case of Li is comparatively less and in case of other than Li is found more, whereas for results of Vora [3] and for results cited in article [1] the situation is inverse. This trend in results favors the results of Thakor et al [14,15].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It also shows that the change in trend, the deviation of our results from experimental values of the internal energy EINT in case of Li is comparatively less and in case of other than Li is found more, whereas for results of Vora [3] and for results cited in article [1] the situation is inverse. This trend in results favors the results of Thakor et al [14,15].…”
Section: Resultssupporting
confidence: 89%
“…Many of the alkali metals have their melting points at or near to room temperature which makes necessary to investigate the properties of elements of this group in the liquid phase. The pseudopotential theory has proven its importance in the study of the liquid metals and alloys [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], but the liquid state of metal is very difficult to study with a very less adjustment in the parameter(s) of model potential because of its complex electron-ion interaction behavior in this state.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they have demonstrated amazing hard and soft sphere structure calculations. They have clarified that the soft sphere model depends on the packing fraction η for the derivation of the structure factor, just like the hard sphere equations [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. They have also calculated the thermodynamic properties of few elements.…”
Section: Ss (Soft Sphere) Methodsmentioning
confidence: 99%
“…Thakor et al [15] demonstrated that the thermodynamic characteristics of liquid alkali metals vary on temperature. The PYHS approach was combined with the Gibbs-Bogoliubov variational technique and the pseudopotential to determine the thermodynamic characteristics.…”
Section: Theory Of Structure Factormentioning
confidence: 99%
“…Here we have introduced some repulsive part outside the core which vanishes faster than only Coulomb potential −Ze 2 /r as r → ∞. Moreover, it may be noted that the inclusion of this repulsive term outside the core makes the effective core smaller than the ionic radius of a free ion [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%